Locally Invasive Primary Splenic Angiosarcoma - Hasiloglu, Zehra Isik (Eurasian J Med, 2010)
Primary angiosarcoma of the spleen is a very rare vascular neoplasm, but it represents the most common non-hematolymphoid malignant tumor of the spleen. In this report, we present the case of a 48-year-old man with primary splenic angiosarcoma with local invasion to the left diaphragm and the radiological imaging findings for this cancer.